2014
DOI: 10.1371/journal.pone.0086812
|View full text |Cite
|
Sign up to set email alerts
|

Tc17 Cells in Patients with Uterine Cervical Cancer

Abstract: BackgroundThe existence of Tc17 cells was recently shown in several types of infectious and autoimmune diseases, but their distribution and functions in uterine cervical cancer (UCC) have not been fully elucidated.MethodsThe frequency of Tc17 cells in peripheral blood samples obtained from UCC patients, cervical intraepithelial neoplasia (CIN) patients and healthy controls was determined by flow cytometry. Besides, the prevalence of Tc17 cells and their relationships to Th17 cells and Foxp3-expressing T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Recent studies indicate that Tc17 cells have important roles in the development and metastasis of tumors (44)(45)(46)(47)(48). Elevated proportions of Tc17 cells in patients with cervical cancers are associated with cancer progression that is accompanied by increased infiltrations of Th17 cells as well as enhanced tumor vasculogenesis and metastasis (44).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that Tc17 cells have important roles in the development and metastasis of tumors (44)(45)(46)(47)(48). Elevated proportions of Tc17 cells in patients with cervical cancers are associated with cancer progression that is accompanied by increased infiltrations of Th17 cells as well as enhanced tumor vasculogenesis and metastasis (44).…”
Section: Discussionmentioning
confidence: 99%
“…Heightened IL-17 expression was documented for several tumors, including hepatocellular carcinoma [21], cervical cancer [31], lung cancer [32], bladder cancer [20], colorectal cancer [22], and others [19]. According to these studies, IL-17 facilitates tumor progression by inducing angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…According to these studies, IL-17 facilitates tumor progression by inducing angiogenesis. For example, increased intra-tumor accumulation of IL-17A-producing cells was associated with an increased vasculogenesis in hepatocellular carcinoma [33], and increased intratumor Tc17 cell activity promoted vasculogenesis in cervical cancer [31]. Furthermore, elevated levels of IL-17A-producing cells was associated with increased lymphangiogenesis in lung cancer [34].…”
Section: Discussionmentioning
confidence: 99%
“…Kondo et al demonstrated that 0.4% of human CD8 + T cells isolated from peripheral blood were capable of expressing IL‐17 when stimulated with PMA and ionomycin. Another group detected Tc17 cells in peripheral blood of patients who had uterine cervical cancer after P/I stimulation and in cervical tissue of the same patients, by immunohistochemistry . In that study, tissue was not stimulated before immunohistochemistry, as the goal was to observe the effect of the cancer on the presence of Tc17 cells.…”
Section: Discussionmentioning
confidence: 99%